Al-Ghazzali – As an Educational Thinker - Peerzada, Najmah (JOURNAL OF INDIAN EDUCATION, 2014)
Al-Ghazzali was one of the greatest philosophers, thinkers and educationists. His philosophy of education laid stress upon the development of personality in which one should also know oneself. He wanted such type of education which would help a person to know himself and his relationship with his God and world. Therefore, education must contribute to the all round development of each individual—mind and body, intelligence, sensitivity, aesthetic sense, personal responsibility and spiritual values. All human beings must be enabled to develop independent critical thinking and form their own judgment. We find Al-Ghazzali forestalling Descartes method of doubt, Hume’s skepticism, Kant’s criticism of pure reason and the spiritual empiricism of some of the philosophers of religion of our own times.